Treatment gap for anxiety disorders is global: Results of the World Mental Health Surveys in 21 countries. Issue 3 (22nd January 2018) - Alonso, Jordi; Liu, Zhaorui; Evans‐Lacko, Sara; Sadikova, Ekaterina; Sampson, Nancy; Chatterji, Somnath; Abdulmalik, Jibril; Aguilar‐Gaxiola, Sergio; Al‐Hamzawi, Ali; Andrade, Laura H.; Bruffaerts, Ronny; Cardoso, Graça; et al.
Abstract : Background: Anxiety disorders are a major cause of burden of disease. Treatment gaps have been described, but a worldwide evaluation is lacking. We estimated, among individuals with a 12‐month DSM‐IV (where DSM is Diagnostic Statistical Manual) anxiety disorder in 21 countries, the proportion who (i) perceived a need for treatment; (ii) received any treatment; and (iii) received possibly adequate treatment. Methods: Data from 23 community surveys in 21 countries of the World Mental Health (WMH) surveys. DSM‐IV mental disorders were assessed (WHO Composite International Diagnostic Interview, CIDI 3.0). DSM‐IV included posttraumatic stress disorder among anxiety disorders, while it is not considered so in the DSM‐5. We asked if, in the previous 12 months, respondents felt they needed professional treatment and if they obtained professional treatment (specialized/general medical, complementary alternative medical, or nonmedical professional) for "problems with emotions, nerves, mental health, or use of alcohol or drugs." Possibly adequate treatment was defined as receiving pharmacotherapy (1+ months of medication and 4+ visits to a medical doctor) or psychotherapy, complementary alternative medicine or nonmedical care (8+ visits). Results: Of 51, 547 respondents (response = 71.3%), 9.8% had a 12‐month DSM‐IV anxiety disorder, 27.6% of whom received any treatment, and only 9.8% received possibly adequate treatment. Of those with 12‐month anxiety only 41.3% perceived a need for care. Lower treatment levels were found for lower income countries. Conclusions: Low levels of service use and a high proportion of those receiving services not meeting adequacy standards for anxiety disorders exist worldwide. Results suggest the need for improving recognition of anxiety disorders and the quality of treatment.